An evaluation of camera trap performance – What are we missing and does deployment height matter?. Issue 4 (8th May 2018) - Jacobs, Caitlin E.; Ausband, David E.
Abstract: The camera trap is a powerful research tool that has a wide range of ecological applications and facilitates monitoring over large spatial and temporal scales. To improve the reliability of camera trap studies and provide more knowledge on camera performance, we evaluated three aspects of camera traps that researchers should consider – camera height, blank images and missed detections. We deployed 20 camera stations, each consisting of one low camera (0.6 m) and two adjacent high cameras (3 m). We tested for differences in detection rates and blank images between camera heights. We calculated missed detections using the two high cameras and used a subset of cameras ( n = 14) to examine whether missed detections were caused by late triggers or failed triggers. We found that placing cameras high to minimize theft and damage did not influence detection rates. There were, however, more blank images which can increase the time required for analysis. These blank images increased as temperature increased. Missed detections were primarily the result of failed triggers and increased as species size decreased. Failed detections are particularly significant for distribution surveys of low‐density species. Detection at the camera is imperfect, even when working with larger species. Abstract : We evaluated three aspects of camera traps that researchers should consider – camera height, blank images and missed detections. We deployed 20 camera stations, each consisting of one low camera (0.6 m) and two adjacent high cameras (3 m). We found that placing cameras high did not influence detection rates and high cameras generated more blank images which increased as temperature increased. Missed detections increased as species size decreased and were primarily the result of failed triggers as opposed to late triggers. We recommend that cameras used for documenting species presence be placed at 2.5 m and above and urge researchers to avoid assumptions of certain detectability inside the detection zone, even when working with larger species.